Perancangan Aplikasi Pemantauan Pendaki Gunung Menggunakan Wireless Network Dengan Protokol MQTT - Feriz Pradibya Uditama; Rakhmadhany Primananda; Mahendra Data (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The increasing cases of missing mountain climbers each year has become a major topic in this case. The last case that can be taken by the author as a reference is the missing climber in Mount Semeru which until now has not been found. From BASARNAS in search of missing mountain climbers so far still uses several methods of searching using drones equipped with thermographic cameras to measure body temperature, using sniffer dogs and the last one is manual with human help. In this study the author tries to find new solutions to help BASARNAS team in searching for the missing climber. The solution offered is the implementation of the publish-subscribe method of mountaineering monitoring system. Mountain area known as area with no reach of internet hence by method of publish-subscribe can facilitate officer to do monitoring of existence of climber. This method allows for data transmission that is by using the help of architectural nodes are interconnected and can be contacted by mobile node belongs to the climbers themselves by utilizing his smartphone. By using this method then the officer will easily find the missing climber's search point. Officers will be able to know the whereabouts of the last climber before being declared lost through the last location information provided by the missing climber. Officers can also request information from other climbers about the missing climber in realtime. Data delivery using the publish-subscribe method will smoothly reach the destination thanks to architectural nodes acting as intermediaries. So far the tests conducted in this study get results in accordance with the purpose of using the method.